Szczepienia ochronne a zapobieganie zakażeniom układu oddechowego - Wysocki, Jacek; Popowicz, Wiktoria; Szymiec, Magdalena (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
Infections of the respiratory tract belong to the most common health problems in the world. Among numerous and different etiological factors two play the dominant role: influenza virus and pneumococci. The characteristics of vaccines against both factors have been presented in the paper and the current recommendations concerning immunizations as well.